Diffuse Large B-Cell Lymphoma (DLBCL): Early Patient Management and Emerging Treatment Options - Vodicka, Prokop; Klener, Pavel; Trneny, Marek (OncoTargets and therapy, 2022)
Diffuse large B-cell lymphoma (DLBCL) represents a curable disease with a 60-70% chance of cure with current R-CHOP chemoimmunotherapy. However, 30-40% of patients are refractory or relapsing. Many attempts failed to improve the outcome of DLBCL patients, including the intensification of R-CHOP regimen, consolidation, or maintenance therapy since the introduction of R-CHOP in 2000. Better understanding of both molecular biology of lymphoma cells and the tumor microenvironment raised the hope for future improvement of DLBCL patients' survival. Novel molecular findings have initiated clinical trials exploring targeted therapy based on driver genetic alterations with an intent to improve survival of high-risk subsets of patients. But the preliminary results remain ambiguous. The approach "agnostic" to specific molecular alterations of lymphoma cell includes antibody-drug conjugates (especially polatuzumab vedotin), immunotherapy comprising different antibodies with immunomodulatory effect (tafasitamab, lenalidomide), and T-cell engaging therapy (bispecific antibodies, early use of CAR T-cell). This approach could increase the cure rates and change the current therapeutic paradigm. However, better prognostic stratification, smarter designs of clinical trials, modification of endpoints including the use of ctDNA are needed. This review covers the complexity of DLBCL management.
Keywords: polatuzumab vedotin; agnostic therapy; R-CHOP; tailored therapy; diffuse large B-cell lymphoma; first-line therapy